Cysteine as Inhibitor on the Corrosion of Mild Steel in Sulphuric Acid and Hydrochloric Acid Solutions - Cang, Hui; Shi, Wenyan; Lu, Yu; Shao, Jingling; Xu, Qi (Asian Journal of Chemistry, 2012)
The corrosion inhibition of mild steel in 0.5 M H2SO4 and 1 M HCl by L-cysteine (Cys) has been studied using potentiodynamic polarization measurements. Inhibition efficiency was found to increase with increasing concentration of L-cysteine in both acids and the higher inhibition efficiency is obtained in 1 M HCl. The activation energy as well as other electrochemical parameters for the inhibition process was calculated. The results suggest that the L-cysteine could serve as an effective inhibition of the corrosion of mild steel in hydrochloric acid and sulphuric acid.